UJI PERFORMA GENERATOR MIKROHIDRO DC ELEKTRIK DALAM PEMANFAATAN EFISIENSI ENERGI PADA HIDROPONIK SISTEM NUTRIENT FILM TECHNIQUE - Arrois Syaifullah; Andhika Dwi Putra; Zanu Saputra; Ocsirendi Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Technological advances in the hydroponic agricultural sector have the potential to be developed. One of them is an electrical energy efficiency system. For this reason, it is necessary to test an appropriate energy source. In this study, the test aims to determine the characteristics of the DC generator, the output of the DC generator will function as a battery charging source which is then used for energy efficiency systems in hydroponics. The test is carried out by comparing the pump height to the DC generator, the incoming water discharge and the DC generator rotation. With a pump height of a DC generator as far as 120 cm and a resistance load of 100 , the flowrate is 1L/minute, the DC generator rotation is 162 rpm and the lowest output power is 0.224 milliWatt. With the pump height to the DC generator as far as 30 cm, the flow rate is 25L/minute, the DC generator rotation is 956 rpm and the highest output power is 0.1 Watt. In other words, the greater the flow/discharge of water that enters the generator, the greater the output produced by the DC micro hydro generator.